A parallel algorithm for the global computation of elastic bar structures - Gáspár, Zsolt; Domokos, Gabor; Szeberényi, Imre (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents an algorithm for parallel computers, which is suitable for the global (arbitrary displacements)computation of elastic bar structures subject to quasi-static loads. Our method is also capableto determine equilibria which are not connected to the initial, trivial configuration. The paper discusses the gains and the disadventages of the method, comparing it with other techniques.